استخدام الجراحة القرية بالآزوت السائل في تدبير التصبغ اللثوي الميلانيني الفيزيولوجي - أمون عمار; علي نورا (Latakia University Journal -Medical Sciences Series, 2017)
تهدف الدراسة إلى تقييم فعالية استخدام الجراحة القرّيّة بالآزوت السائل في علاج المشكلة التجميلية الناجمة عن التصبغ اللثوي الميلانيني. تألفت عينة البحث من 20 مريض راجعو قسم طب الفم في كلية طب الأسنان ممن يعانون من تصبغ لثوي ميلانيني فيزيولوجي في الفترة بين 1 تشرين الثاني 2013 و1 نيسان 2016، تضمنت المراقبة السريرية أخذ صور ضوئية للمرضى قبل وبعد 3 أشهر،و6 أشهر، وسنة من تطبيق الإجراء، واستخدم مشعر التصبغ اللثوي لـ Dummett لقياس مقدار التصبغ، واستخدم اختبار T-student للعينات المقترنة في تحليل البيانات. تم تطبيق العلاج على اللثة المصطبغة مع الحد الأدنى من الإنزعاج للمريض وكان الشفاء التالي خالٍ من المضاعفات وغير مؤلم. أظهر التحليل الإحصائي للبيانات وجود فرق معنوي بين مقدار التصبغ قبل وبعد التطبيق. بالنتيجة يمكن اعتبار تقنية الجراحة القرّيّة باستخدام الآزوت السائل طريقة فعالة وآمنة لإزالة التصبغ اللثوي الميلانيني. The aim of the study was to assesst the effect of cryosurgery by means of liquid Nitrogen LN to manage the aesthetic problem caused by gingival melanin Pigmentation (GMP). The study is composed of 20 patients who attended the department of oral medicine at Tishreen University, Lattakia- Syria. Their chief complaint was GMP between November 1st 2013 and April 1st 2016. The clinical observation included caputuring photographs pre-procedure and 3 months, 6 months and a year post-procedure. Dummett Oral Pigmentation Index (DOPI) was used as a reference to indicate the colour of the pigmented areas degrees, and statistical analysis was performed by T-student test for paired samples. Ablation of hyperpigmented gingiva was accomplished with minimal discomfort and post-procedure healing was uneventful and with no post-pain. Such statistical study revealed a significant difference between pre- and post-procedure measurements of pigmented areas. In conclusion, the application of cryosurgery using LN appears to be an effective and safe method for elimination of GMP.